The Protein/Carbohydrate Ratio in the Diet Affects Zootechnical Performance and the Regulation of Intermediary Metabolism in Juveniles Tambaqui (Colossoma macropomum) - Carli, Gabriela Castellani [UNESP]; Palma, Mariana; Satiro, Thaise Mota [UNESP]; Soares, Hugo Henrique D'Amore [UNESP]; Ferrari, Jeisson Emerson Casimiro [UNESP]; Viegas, Ivan; Takahashi, Leonardo Susumu [UNESP] (Wiley, 2024)
The use of carbohydrates in animal feed is a way to save protein in the diet. This study evaluated the effect of protein/starch ratio on the performance, hepatic metabolism, and body composition of juvenile tambaqui (Colossoma macropomum). Six isoenergetic experimental diets were formulated containing three levels of digestible protein (P: 230, 260 and 290 g kg−1) and two levels of starch (S: 180 and 280 g kg−1): P23S18, P23S28, P26S18, P26S28, P29S18 and P29S28. Juveniles tambaqui (N = 288; initial weight = 30.0 ± 3.8 g) were fed experimental diets for 90 days and the zootechnical performance was evaluated. Nine fish from each treatment group were sampled to determine somatic indices, blood metabolites, tissue energy reserves, body composition and activity of key hepatic enzymes. Blood triglycerides, hepatosomatic index, liver and muscle lipids, and hepatic glycogen increased significantly with starch while blood glucose, triglycerides and cholesterol, muscle lipids were significantly impacted by protein levels. Fish-fed S28 had increased feed intake (1714–1829 g; p < 0.0001) and fish-fed diet P26S18 had a higher protein efficiency rate (23.62%; p = 0.0356). Fish fed P23 had lower crude protein retention in the carcass (p = 0.0018) and high lipogenesis and lipid deposition in the muscle (p = 0.0069). These results suggest that dietary carbohydrates have a protein-sparing effect. Tambaqui adapted well to diets containing starch, even at higher levels, resulting in an overall increase in lipogenesis from S18 to S28. Thus, we recommend P26S18 as a cost-effective feed that ensures both zootechnical performance and quality of the final product.
Keywords: growth; lipogenesis; metabolism; protein sparing; starch; tambaqui